Understanding Pathways from Cognitive Biases to the Risk of Psychosis: A Network Analysis Approach - Xi C; Wang S (Psychology Research and Behavior Management)
Chang Xi,1 Song Wang2 1Department of Psychology, Hunan University of Chinese Medicine, Changsha, People’s Republic of China; 2College of Information and Intelligence, Hunan Agricultural University, Changsha, People’s Republic of ChinaCorrespondence: Chang Xi, Department of Psychology, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People’s Republic of China, Email xichang_92@163.comPurpose: Although the linkage between cognitive biases and psychotic-like experiences (PLEs) is well established, the knowledge of potential mechanisms of this relationship is still unknown. The aim of the present study was to better understand the structure of connections between cognitive biases and PLEs by considering at the same time the role of childhood trauma and depressive symptoms in a non-clinical adolescent sample (aged 14– 19 years).Methods: PLEs were measured using the Community Assessment of Psychic Experiences (CAPE-P15), cognitive biases were assessed with the Davos Assessment of Cognitive Biases Scale-42 (DACOBS-42), depressive symptoms were evaluated using the Patient Health Questionnaire-9 (PHQ-9) and exposure to childhood traumatic life events was measured using the Childhood Trauma Questionnaire (CTQ-SF). A network analysis was conducted to examine the interrelationships between these variables.Results: The most central nodes in the network were the cognitive bias items “belief inflexibility”, “safety behaviors”, and “subjective cognitive problems”. Shortest path analyses revealed that depressive symptoms played a significant mediating role between cognitive biases and PLEs. Specifically, the shortest pathways from cognitive biases item “subjective cognitive problems” to PLEs items P7 (subjective cognitive problems), P8 (thought own), and P11 (control force) involved depressive symptoms, including items related to “guilt”, “concentration”, “motor”, and “ suicide”.Conclusion: Our findings highlight the central role of cognitive distortions and emotional symptoms within the psychosis-risk network. Depressive symptom nodes serve as critical mediators between subjective cognitive problems and PLEs, underscoring their pivotal function in driving the development of PLEs among adolescents with cognitive biases. These results suggest a tight interconnection between emotional and cognitive processes in psychosis vulnerability, emphasizing the need for integrated interventions targeting both domains.Keywords: psychotic-like experiences, depressive symptom, childhood trauma, adolescents